Structural and buckling behavior of full-scale slender UHPC columns. (15th March 2022) - Aboukifa, Mahmoud; Moustafa, Mohamed A.
Highlights: Full-scale testing of five UHPC columns with various slenderness ratios under axial loads. Investigate buckling behavior and its effects on structural response. Assess ACI 318 procedures for analysis and design of slender UHPC columns. Propose design guidelines to be used exclusively for UHPC columns. Abstract: Ultra-high performance concrete (UHPC) is a relatively new class of concrete and cementitious materials with much higher strength and durability than conventional concretes. The use of UHPC is currently expanding worldwide from bridge deck joints and connections to full components and larger applications. With the superior mechanical properties of UHPC, future UHPC columns in buildings and bridges will have compact cross-sections and smaller footprint. The main goal of this study is to provide experimental demonstration and reliable datasets of slender UHPC columns to validate current analytical procedures and inform future designs. This paper presents results and discussions from five full-scale UHPC columns (largest set of axially-tested UHPC columns to-date) at a 4 million-lb [∼18, 000 kN] testing facility. The specific objectives are to investigate the structural and buckling behavior of slender UHPC columns under concentric axial loading, and assess the current ACI procedure for slenderness effects using the moment magnification method. When the actual material properties of UHPC and longitudinal bars are used for assessment, the ACI equations were found to overestimate the axial load capacity of slender columns by approximately 9%, on average. The study is concluded by design guidance and several recommendations for applying the moment magnification method for slender UHPC columns, which can be readily incorporated into future design codes.